CROWDFUNDING: ESSENCE AND FACTORS AFFECTING ITS DEVELOPMENT - Давидовська, Галина Іванівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
In the developed world, crowdfunding is considered an innovative high-tech financial instrument for raising funds to implement projects and support startups. This method of financing has many advantages, but its application in Ukraine is somewhat limited due to certain technological, economic and social barriers. The need for a detailed study of the concept of «crowdfunding», its features and conditions of operation is precisely due to the existence of these problematic aspects. The aim of the article is to study the economic essence of crowdfunding, the factors that influence the formation and development of crowdfunding systems in the world. To achieve this goal, various general and special methods of scientific research were used: analysis, synthesis, grouping, comparison and generalization – to clarify the conceptual and categorical apparatus, in particular, to substantiate the essence of the concepts «crowdfunding», «crowdfunding system», «crowdfunding activity», as well as during the improvement of the typology of factors of crowdfunding formation, graphic – for visual display of research results. The article improves the typology of factors for the development of crowdfunding. In contrast, the existing classification distinguishes two key groups of factors: general (state of the banking system, income level, development of the market of payment cards and electronic systems, entrepreneurial activity, shadowing of the financial sector, availability of credit products for entrepreneurs and young enterprises) and special (middle class in the country, the propensity of the population to save, the state of public confidence in innovative socio-economic instruments, the motivation of the population to microinvestment, the state of financial and technical literacy of citizens, etc.). Also, the conceptual and terminological apparatus for crowdfunding systems was further developed, which, in contrast to the current ones, takes into account the method of attracting financial resources and the peculiarities of their activities. In particular, the concept of «crowdfunding» should be considered as an innovative tool that allows you to accumulate financial resources from a large number of participants (donors) to implement project authors (recipients) innovative, social and business projects using specialized Internet resources; «Crowdfunding» – is a type of business activity that mobilizes financial and other resources through specialized Internet resources from various sources to implement innovative, social and business projects, which requires special competencies from the authors of projects (recipients) who have the opportunity to influence to make positive decisions of the donor.